More sustainable use of aquaculture cleaner fish: collagen-rich protein hydrolysates from lumpfish (Cyclopterus lumpus) – effects of biomass, pretreatment, and enzyme choice - Lian, Kjersti; Maribu, Ingrid; Rode, Tone Mari; Jenssen, Marte; Vang, Birthe; Solstad, Runar Gjerp (Frontiers in Sustainable Food Systems, 2024)
Farmed lumpfish (Cyclopterus lumpus) are used as cleaner fish in Norwegian aquaculture. However, once the fish reaches sexual maturity, it becomes less effective in combating lice and is often wasted or turned into silage. This raises ethical, economic, and sustainability concerns regarding whether the use is sustainable without increasing its standard of living and further use of the fish to higher value products. To improve the utilization of lumpfish, a study was conducted to investigate the differences in extraction efficiency by comparing product yield, protein content, and peptide size distribution after enzymatic hydrolysis of lumpfish using several commercial proteases (Corolase 8,000, Corolase 7,089, Endocut 01 L, Flavourzyme, and Food Pro PNL), and different pretreatment methods (pulsed electric field and high-pressure processing). The choice of enzyme did not affect the amino acid contents of the different hydrolysates. Furthermore, varying enzyme concentrations had a minor impact on the final product’s protein content. As anticipated, increased enzyme concentrations decreased the hydrolysates’ average molecular weight. The study found that biomass treated either chemically (NaOH and butanol) or mechanically with a pulsed electric field before enzymatic hydrolysis resulted in higher protein content and relatively higher amounts of collagen peptides. Initial bioactivity testing indicated that the hydrolysates had no toxic effects on hepatocellular carcinoma and non-malignant lung fibroblast cells. Previous studies have shown that farmed lumpfish contains all the essential amino acids and has high levels of EPA, DHA, B12, and D3 vitamins. The contents of environmental pollutants and heavy metals were also below the EU maximum levels. This study’s knowledge and results open for the potential use of lumpfish peptides and gelatin for, e.g., dietary supplements, feed, and biodegradable packaging.